Suppression of β-catenin and cyclooxygenase-2 expression and cell proliferation in azoxymethane-induced colonic cancer in rats by rice bran phytic acid (PA) - Saad, Norazalina; Mohd Esa, Norhaizan; Ithnin, Hairuszah (Asian Pacific Organization for Cancer Prevention, 2013)
Background: Phytic acid (PA) is a polyphosphorylated carbohydrate that can be found in high amounts in mostcereals, legumes, nut oil, seeds and soy beans. It has been suggested to play a significant role in inhibition of colorectal cancer. This study was conducted to investigate expression changes of β-catenin and cyclooxygenase-2 COX-2) and cell proliferation in the adenoma-carcinoma sequence after treatment with rice bran PA by immunocytochemistry. Materials and Methods: Seventy-two male Sprague-Dawley rats were divided into 6 equal groups with 12rats in each group. For cancer induction two intraperitoneal injections of azoxymethane AOM) were given at 15 mg/kg bodyweight over a 2-weeks period. During the post initiation phase, two different concentrations of PA, 0.2%(w/v) and 0.5% (w/v) were administered in the diet. Results: Results of ß-catenin, COX-2 expressions and cell proliferation of Ki-67 showed a significant contribution in colonic cancer progression. For ß-catenin and COX-2 expression, there was a significant difference between groups at p<0.05. With Ki-67, there was a statistically significant lowering the proliferating index as compared to AOM alone (p<0.05). A significant positive correlation (p=0.01) was noted between COX-2 expression and proliferation. Total ß-catenin also demonstrated a significant positive linear relationship with total COX-2 (p=0.044). Conclusions: This study indicated potential value of PA extracted from om rice bran in reducing colonic cancer risk in rats.